Theoretical and methodological support of educational process of students-powerlifters using Internet resources - Stetsenko Anatolij Ivanovich (Kharkov National Pedagogical University, 2011)
It is reviewed scientific journals that have free public access. Investigated the information resources of powerlifting on the internet. Accentuated the importance of using professionally-oriented information resources in the learning process. It is established that Ukrainian language environment of the internet in the sphere of powerlifting has been relatively much attention in comparison with other power sports. Formed the base of internet resources for students of physical culture and sports institutions that specialize in powerlifting. The need to continue and complete the work to create an electronic library on physical education and sport.